2021
DOI: 10.33552/wjass.2021.06.000643
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sweet Potato (Ipomoea Batatas (L) Lam) Varieties at Tepi, Southwestern Ethiopia

Abstract: Sweet potato (Ipomoea batatas (L.) Lam.) is one of the globally important root crops. In Ethiopia, its production is confronted with lack of planting materials, shortage of farmer preferred varieties, poor extension system among many other constraints. The study was conducted to assess the performance of different released varieties at Teppi. Evaluation of the varieties was carried out in main cropping season. Each treatment was replicated three times and arranged in Randomized Complete Block Design. Stand cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…In terms of locations, Jamalpur recorded the longest average root length at 16.27 cm, whereas Chattogram had the shortest average storage root length at 13.07 cm. These findings align with the research conducted by Shamil [ 18 ], who reported significant variations in root length among six studied varieties, ranging from 8.9 cm to 24.8 cm, highlighting the considerable variability across different genotypes. Rashid et al [ 19 ], Rahman et al [ 20 ], Rafique et al [ 21 ], Reddy et al [ 22 ], and Hayati et al [ 23 ] all reported that the length of the storage roots varied across varieties.…”
Section: Resultssupporting
confidence: 92%
“…In terms of locations, Jamalpur recorded the longest average root length at 16.27 cm, whereas Chattogram had the shortest average storage root length at 13.07 cm. These findings align with the research conducted by Shamil [ 18 ], who reported significant variations in root length among six studied varieties, ranging from 8.9 cm to 24.8 cm, highlighting the considerable variability across different genotypes. Rashid et al [ 19 ], Rahman et al [ 20 ], Rafique et al [ 21 ], Reddy et al [ 22 ], and Hayati et al [ 23 ] all reported that the length of the storage roots varied across varieties.…”
Section: Resultssupporting
confidence: 92%
“…However, EBO/SP 5 and NSPO 2012-005 showed poor performance in most of traits in the study. 33 found variations in the average number of roots per plot, with Kulfo varieties having the lowest average root number per plot and local and Beletech varieties having the highest. 34 also noted a signi cant variation in the number of roots per plant.…”
Section: Cluster Analysismentioning
confidence: 95%
“…Its' large starchy , and sweet tasting roots are an important edible part. It produces storage roots which are rich in carbohydrate, vitamins such as A, B complex, C, E and minerals such as potassium, calcium and iron [1]. The young leaves and…”
Section: Introductionmentioning
confidence: 99%